DESDE LA COEXISTENCIA DE MODELOS DE REPRESENTACIÓN, HASTA LA CRISTALIZACIÓN DE UN NUEVO MODELO: LA VENTANA INDISCRETA - Francisco Manuel Sánchez Sánchez, (Fonseca, Journal of Communication, 2023)
Noël Burch stablished the basis for the systematization of the different models of cinematographic representation. The essential focus of his arguments, which were exposed in The skylight of infinity, is that the different models of representation are distinguished by the position of the viewer on the narration.